Does Varicocelectomy Improve Gonadal Function in Men with Hypogonadism and Infertility? Analysis of a Prospective Study - Vasan Sathya Srini; Srinivas Belur Veerachari (International Journal of Endocrinology)
Varicocele in infertile males is associated with Leydig cell dysfunction and hypogonadism. The effect of varicocelectomy on serum testosterone level is not yet established. We analysed 200 heterosexual infertile men diagnosed to have clinical varicocele they were divided into two groups: group 1 (100 men) had microsurgical varicocelectomy, and group 2 (100 patients) underwent assisted reproduction procedures. All participants had semen analysis, serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, and total testosterone (TT), measured both at recruitment time and 6 months later. In group 1, the mean TT level increased significantly after varicocelectomy (1.644±0.029 to 2.461±0.0198 ng/dL, P<0.0001) and testicular size correlated with the mean change in TT (P=0.001). No similar change was found in group 2. Out of the 100 patients in group 1, 78 had postoperative normalization of TT unlike only 16 men in group 2.